(untitled) (The Pakistan Development Review, 2003)
In Pakistan all the macro indicators have been adversely affected by the persistently high deficits and the strategy adopted to finance them in the last two decades. The excessive domestic borrowing at high rates to finance deficits without any attempts at domestic resource mobilisation and controlling of the deficits over extended periods absorbed all available domestic and external resources. The resulting debttrap led to increased external borrowings at high rates with short-term maturity. This, coupled with massive exchange rate depreciation throughout the last two decades, resulted in rapid debt accumulation. The recent fiscal space created in the wake of events of 9/11, resulting in high reserves, follows considerable debt relief and availability of massive funds on very soft terms. However, the decline in budget deficit continues to occur at the expense of development expenditure, along with some increase in tax revenues. This trend in expenditure needs to be reversed if serious progress in debt reduction is the aim.